ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE Tbk - Sumita Widiyah Ningsih (Jurnal Manajerial Bisnis, 2023)
This study aims to examine and analyze the analysis of financial ratios to financial distress with firm value as an intervening variable in property and real estate companies Tbk. This type of research is quantitative with the population in this study as many as 65 companies within a period of 3 years, namely 2018 - 2020. The sample companies are 30 companies. Purposive sampling sampling technique. This study uses secondary data published by the Indonesia Stock Exchange. Data analysis was carried out with a quantitative approach using path analysis. Path analysis to test and prove the research hypothesis. The results showed that profitability, liquidity, solvency and activity had no significant effect on firm value; profitability and activity have no effect on financial distress; liquidity, solvency and firm value affect financial distress; Profitability has no effect on financial distress through firm value, while liquidity, solvency and activity affect financial distress through firm value.